Perencanaan Angkutan Umum Perkotaan Berkelanjutan - Ahmad Munawar (Unisia, 2006)
The realization of  public transportation in cities in Indonesia has some obstacles. The problems cover services because of high operational cost, the decrease of  passengers, and the safety in public transportation. The weakness of public transportation also grows the informal sectors in this sector. The comparative analysis regarding public transportation between Yogyakarta and Bandung including net way, vehicles, head way, load factor, the quality and the obstacle. Hence, to build cities public transportation either in short, middle and long term. Theses terms cover the sustainability, buy service system, and massive public transportation system.